Precision Medicine—Nobody Is Average. Issue 3 (March 2017) - Vinks, AA
Abstract : Medicine gets personal and tailor‐made treatments are underway. Hospitals have started to advertise their advanced genomic testing capabilities and even their disruptive technologies to help foster a culture of innovation. The prediction in the lay press is that in decades from now we may look back and see 2017 as the year precision medicine blossomed. It is all part of the Precision Medicine Initiative that takes into account individual differences in people's genes, environments, and lifestyles.